Eco-friendly synthesis of reduced graphene oxide from agricultural waste for electrodes in capacitive deionization applications - Penpicha Poonpat; Teerayut Uwanno; Voragun Tajorn; Setthaphon Bodsayawit; Mayuree Phonyiem Reilly; Winadda Wongwiriyapan (Journal of Physics Conference Series, 2025)
Abstract In this study, reduced graphene oxide (rGO) was synthesized from sugarcane bagasse (SB) through dehydration of SB by concentrated H 2 SO 4 , graphene oxide (GO) formation by modified Hummers’ method and reduction by anthocyanin in pomegranate juice. It was found that rGO that underwent reduction reaction for 24 hours has highest carbon/oxygen ratio from elemental composition from X-ray photoelectron spectroscopy (XPS), suggesting the highest degree of reduction among all reduction time. The formation of rGO was confirmed by UV-visible absorption spectrum, XPS, Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy.
Keywords: Membrane-based Ion Separation Techniques; Membrane Separation Technologies; Recycling and Waste Management Techniques